Fostering bacterial growth in BFT aquaculture tanks by early Nile tilapia stocking - Francisco Roberto dos Santos Lima; Davi de Holanda Cavalcante; Marcelo Vinícius do Carmo e Sá (Acta Scientiarum. Animal Sciences, 2021)
The current study aimed at fostering bacterial growth in BFT aquaculture tanks by early Nile tilapia stocking. Control tanks had no tilapia but received daily applications of dry molasses (NT+) or had tilapia but no C:N ratio adjustment (T-). Experimental tanks had tilapia and received daily application of molasses to adjust the C:N ratio of water to 15:1 (T+). The development of bioflocs in NT+ was insignificant as demonstrated by low levels of settleable solids (SS) and total suspended solids (TSS). Total ammonia nitrogen (TAN) was significantly higher in NT+ than in T+. In the C:N-ratio adjusted tanks, the presence of fish shortened the control of TAN in several days. As nitrite declined in T+, it increased in NT+. The final concentrations of TSS in T+, T- and NT+ were 236 ± 29 mg L-1, 100 ± 32 mg L-1, and 40 ± 22 mg L-1, respectively (p < 0.05). It can be concluded that stable nitrifying and heterotrophic bacterial communities could be attained in BFT aquaculture tanks, before the end of the 4th week of culture, if the bacterial growth is fostered by early Nile tilapia stocking.